Imported Schistosomiasis in Children: Clinical, Diagnostic Aspects And Outcome in 5 Tertiary Hospitals in France. Issue 12 (December 2017) - Leblanc, Claire; Pham, Luu-ly; Mariani, Patricia; Titomanlio, Luigi; El Ghoneimi, Alaa; Paris, Luc; Escoda, Simon; Lottmann, Henri; Toubiana, Julie; Paugam, André; Ulinski, Tim; Bouchaud, Olivier; et al.
Abstract : The objective of this retrospective study is to describe imported schistosomiasis in children in the Paris region between 2010 and 2015. Forty children with a diagnosis of schistosomiasis were included. Thirty-seven (93%) had a chronic urinary form with hematuria. The lost-to-follow up rate for the second consultation was 25%. The diagnosis and management of imported schistosomiasis must be improved—notably by raising awareness among clinicians and providing families with more information.